DETERMINANTS OF SAVINGS AND INVESTMENT AMONG COCOA FARMERS IN BOKI LOCAL GOVERNMENT AREA OF CROSS RIVER STATE, NIGERIA - Fakuta, Balthiya Alfred; Ofem, Uket Ikpi; Ajah, Eucharia Agom; Ohen, Susana Ben (FUDMA JOURNAL OF SCIENCES, 2026)
This study examined the determinants of savings and investment among cocoa farmers in Boki Local Government Area, Cross River State, Nigeria. Specifically, the study identified the different forms of saving and investment, examined the socio-economic factors influencing savings, analysed the determinants of investment and identified the constraints affecting savings and investment decisions of cocoa farmers. A multi-stage sampling technique was employed to select 120 cocoa farmers and primary data was obtained through structured questionnaire. Data was analysed using descriptive and inferential statistics. Results showed that 70% of respondents were male, 70.8% married, and 49.2% within the economically active age group (40–59 years), reflecting a labour-intensive, experience-driven production system. About 68.3% used formal financial institutions for savings, while 62.5% invested in land and real estate due to perceived security and long-term value. Regression results indicated that income (p < 0.01), farm size (p < 0.05), and farming experience (p < 0.05) significantly influenced savings, while age, marital status, farming experience, and income significantly influenced investment decisions. These patterns reflect income capacity and life-cycle dynamics. However, price volatility, high input costs, and poor infrastructure constrained financial accumulation. The study concludes that savings and investment among cocoa farmers are primarily income-driven but structurally constrained. It recommends strengthening rural financial systems, stabilizing agricultural incomes, and improving infrastructure to enhance farmers’ capacity for sustainable investment.
Keywords: Cocoa farmers; Savings; Investment; Socio-economic determinants; Nigeria; Rural development